2012
DOI: 10.1016/j.jdent.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Properties of dental resins submitted to pH catalysed hydrolysis

Abstract: To accelerate composite hydrolysis and produce quick in vitro microstructural damage, alkaline medium appears to be more suitable than acidic medium. Contemporary resin composite properties seem to withstand neutral and acidic oral environments tolerably well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 19 publications
5
59
1
3
Order By: Relevance
“…There is limited evidence to support significant degradation of dental adhesives at low pH 10, 69 . Results suggest that the degradation of resin-based dental materials occurs at similar rates in water, artificial saliva and in neutral to slightly low pH media 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence to support significant degradation of dental adhesives at low pH 10, 69 . Results suggest that the degradation of resin-based dental materials occurs at similar rates in water, artificial saliva and in neutral to slightly low pH media 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of this reaction is fast or slow depending on the type of chemical bond, pH, and water uptake 9 . In general, the hydrolysis reaction is expected to be relatively slow at the neutral pH typical of saliva, but excursions in pH caused by foods or cariogenic bacteria may lead to transient acid or base catalysis 10 . Local domains of the polymethacrylate networks may become sufficiently degraded and/or hydrophilic to permit access by esterases, which will accelerate ester bond hydrolysis 11, 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This deterioration leads to stress and crack growth, thereby resulting in a rapid increase in the amount of water absorbed by the composite material due to silane hydrolysis and degradation 20,36) . Cilli et al 12) found that water uptake by filled specimens is approximately twice that in an unfilled resin. This behavior is attributed to an accumulation of water between the filler/matrix interfaces because of the slow development of superficial flaws related to preexistent corrosive processes.…”
Section: Hydrolytic Degradation Of Silanementioning
confidence: 98%
“…Adding a small amount of titanates can improve bond strength and moisture resistance 11) . Resin composites are widely used in restorative dentistry, and satisfactory clinical performance is largely determined by their resistance to degradation in the oral environment 12,13) . The mechanical properties of resin composites are influenced by their chemical composition and type of environment that they are exposed to.…”
Section: Introductionmentioning
confidence: 99%
“…The first step in this process is the absorption of water that internally diffuses through the matrix and can lead to softening and degradation, putting some properties such as the roughness of these composites at risk [21]. Despite the high hydrophobic content in the resin matrix of the nanofilled composite tested in this investigation, the presence of TEGDMA makes it sensitive to the absorption of water [1,19].…”
Section: Resultsmentioning
confidence: 94%